The Sociolinguistic Analysis of Dad Joke on the Youtube Channel Yeahmad - Prabu Sulaiman Syahputra; Sastika Seli; Dewi Syafitri (Institute of Advanced Knowledge and Science, 2024)
This research aimed to analyze the type of dad joke that appeared on the YeahMad YouTube Channel. The researcher used descriptive qualitative method to collect the data through watching the chosen videos and take a note. The researcher took the 7 chosen videos specifically with dad joke segment as a sample to take the data. The sample of the data were published videos in a span of time from January to June 2024. The fundamental and particular theory of dad jokes that is unavailable was utilized by the researcher to carry out this research. Meyer's (2015) theory of the seven varieties of jokes includes wordplay, irony, sarcasm, situational humor, canned jokes, anecdotal humor, and self-deprecating humor. The data were analyzed and classified by using the theory by Meyer which was the type of jokes. The results showed that the researcher found 109 dad jokes that can be analyzed and classified into the type of jokes which were 12 anecdotal, 19 canned jokes, 11 situational, 4 self-deprecating, 29 wordplay jokes, 14 irony jokes, and 20 sarcasm jokes. Overall, the dad jokes in YeahMad YouTube videos can be classified into the type of joke based on Meyer, which is anecdotal, canned, situational, self-deprecating, wordplay, irony, and sarcasm.